INVESTMENT RESOURCES OF THE BUSINESS ENTITIES OF TATARSTAN REPUBLIC - R. M. Nurimukhametov (Russian Journal of Economics and Law)
The investment activity efficiency depends on the development of the internal investment sources, among which a special role is played by the enterprise's investment capability and the production crediting system. The article views the features of the internal investment resources attraction in the Republic of Tatarstan.